Exploring Investment Decision-Making with CAPM: Case Studies on Ten Raw Materials Companies Listed in Stock Exchange - Haq, Fadiah Hasna Nadiatul; Sukono, Sukono (Indonesian Operations Research Association (IORA), 2024)
The investment business in Indonesia experienced significant growth in line with the increasing stock trading activity in the capital market. The large number of capital markets in Indonesia means investors have to be careful in determining the shares to be chosen. Based on transaction value, the raw materials sector is the second largest sector that supports the Indonesian capital market. Given the large number of issuers in the raw materials sector, determining investment portfolios is important to obtain optimal results. CAPM can classify stocks as efficient or not based on their expected return value. The results obtained can be used as a consideration in portfolio decision-making. This research identifies 10 stocks in the raw materials sector listed on the IDX. Of the 10 stocks studied, 8 are included in the efficient category, which has a greater return than expected, and 2 are included in the inefficient category. This means that investors who want to invest in raw materials can make a decision to buy these 8 stocks, and it is not recommended to buy shares in 2 inefficient category stocks or sell 2 stocks.